Factors Associated With the Intention to Participate in Coronavirus Disease 2019 Frontline Prevention Activities Among Nursing Students in Vietnam: An Application of the Theory of Planned Behavior - Tran, Quynh Anh; Nguyen, Huong Thi Thanh; Bui, Tung Van; Tran, Nguyet Thi; Nguyen, Nguyet Thi; Nguyen, Tham Thi; Nguyen, Hien Thu; Nguyen, Son Hoang (Frontiers in Public Health, 2021)
Introduction: Medical students have been serving as a key part of the frontline health workforce responding to the coronavirus disease 2019 (COVID-19) pandemic globally. Their contribution is especially important in the resource-scarce settings of developing nations such as Vietnam. Yet, the intention of medical students, in particular, nursing students, to participate in COVID-19 frontline prevention activities has not been well-understood. This study aimed to examine factors associated with the intentionto participate in COVID-19 frontline prevention activities among Vietnamese nursing students. Methods: A cross-sectional study was conducted on a total of 597 students in December 2020 in Hanoi, Vietnam. Information regarding the socioeconomic characteristics of participants, their source of COVID-19 related knowledge, and their perception and attitude toward participating in COVID-19 frontline activities [based on Theory of Planned Behavior (TPB)] was collected. A hierarchical regression model was employed to examine the association between intentions of students and associated factors. Results: A positive intention to participate in COVID-19 frontline prevention activities was found (mean score of 25.3 over 35; SD = 4.4; min = 5; max = 35). Attitude toward behavior, subjective norms, and perceived behavioral control (PBC) was found to be significantly associated with the intention of students. These variables explained the 37% variation in the intention of students in the model. Among three factors, subjective norm showed the strongest correlation with intention of students (β = 0.358; p < 0.001). Obtaining information from official sources and community was also found to be positively correlated with intention to participate. Conclusion: Most of the respondents reported a positive intention to participate in COVID-19 frontline prevention activities. The findings suggested that the TPB was a good instrument to predict the intention to perform behavior among Vietnamese students. Enhancing the positive attitude of students, encouraging family and community supports, and providing adequately essential resources will contribute to optimizing the participation of students to confront COVID-19.